An inquiry into the nature of effective dialogue and discourse and peacebuilding through leadership - Mwagiru, Nyambura (GSB: Faculty, 2016)
The research study and findings presented in this work underscore the necessity to design and develop effective strategies for inter-paradigm dialogue and discourse for peacebuilding. The study argues that adoption and application of appropriate dialogue strategies impact and engender the nurturing and emergence of a culture of leadership that can foster sustainable peace. Dialogue and discourse processes are considered as being intricately connected to processes of conflict transformation and resolution, and linkages of dialogue, peacebuilding and leadership are mirrored in macro- and micro- spaces of engagement, namely, much contested cultural, political and economic spaces in which myriad and diverse perspectives reside. The potential for peace, it is argued, substantially lies in the formulation and design of contextually-relevant frameworks for equitable and sustainable socio-economic development, and macro-micro intersections play themselves out in the dialogue field within which societies and individuals can seek and strive to anticipate, accommodate, attain and enact their life wisdoms into peaceful systems of co-existence. This view also speaks to the issue of how consensual and sustainable global and regional collaborative enterprise requires the parallel accompaniment of well-configured partnerships in support of cultural responsiveness and social cohesion. Through discussion of appropriate methodologies of dialogue and discourse, the identification and statement of objectives for this study, as well as the design, elaboration and configuration of its research framework, aimed to contribute towards furthering debate surrounding the integration of prevailing theoretical approaches, in order to gain a better understanding of the linkages and dynamics between peacebuilding initiatives, conflict resolution processes, and effective and sustainable leadership. Dialogue is adopted as the key component in the design of an effective model and architecture for peace building. The enquiry underscores emerging gaps that require addressing, and which may then highlight zones of ambiguity, or dialectics between action and practice, and between researcher and practitioner.